Efficiency improvement of polystyrene-based plastic scintillators - Adadurov, A.F.; Zhmurin, P.N.; Lebedev, V.N.; Titskaya, V.D. (Functional Materials, 2009)
The radiationless energy transfer mechanisms between energy donor and acceptor have been studied to determine the character of their spatial distribution. The observed deviation of luminescence decay law from the root dependence indicates a inhomogeneous distribution of p-terphenyl in a polystyrene block. This inhomogeneity is due to p-terphenyl expelling from internal volume of a polystyrene macromolecule. Therefore, one way to improve the scintillation efficiency is to provide a more homogeneous distribution of activator in a scintillator block. This can be realized in a system including a plastic copolymer and the activator molecules.